(untitled) - Cashman, Kenvin (Hoboken, N.J., 2003)
More Than a Book. . . . An Interactive Coaching Experience A spiritual journey that will take you to a new and inspiring understanding of leadership." "Kevin Cashman’s storytelling draws you in and forces you to explore the inner and outer terrain of your life and how it impacts the whole. It’s refreshing to read a business book that motivates and provides the practices to become a more conscious leader, yet allows enough space to interpret your own legacy." "It is often said that we live our lives in the present but understand them in the past. Awakening the Leader Within is a terrific reflection and self-coaching tool to close the insight gap which often stands in the way of maximum success and personal fulfillment." "Once you start reading Awakening the Leader Within, you won’t set it down. Cashman doesn’t let you off the hook until you contemplate how you will live your life differently."
Keywords: Leadership,Executives,Management; Philosophy,Training of,Philosophy